AN ANALYSIS OF ILLOCUTIONARY ACTS USED BY THE CHARACTERS FOUND IN AFTER MOVIE - Apriesa, I Dewa Gede Fernanda Aditya; Candra, Komang Dian Puspita; Jayantini, I. G. A Sri Rwa (Apollo Project: Jurnal Ilmiah Program Studi Sastra Inggris, 2023)
This research aimed about the types of illocutionary acts found in After movie. The researcher used the theory from Searle (1976) in order to find out the types of illocutionary acts. Meanwhile, to analyze the meaning based on the context of situation, the researcher used the theory from Halliday and Hassan (1985). The main data source of this study is After movie. Observation method and note taking technique are used in this study to collect the data. This study used descriptive qualitative method in analyzing the types of illocutionary acts and the meaning based on the context of situation. In this research there are 27 data were found in After movie. All the types of illocutionary acts were found in this research which are Assertive, Directive, Commissive, Expressive and Declarative. The meaning of illocutionary acts supported by the context of situation which are Field, Tenor and Mode. Keywords: Illocutionary acts, Characters, Meaning, Movie